Assessment of a novel activity of Acacia nilotica leaf extract for chondrogenesis induction of Mesenchymal stem cells for dental applications - Yasir B. Fadhil; Mohammed Hadi Jaber; Hind M. Ahmed (Elsevier, 2021)
Background: The Dearth of the self-rejuvenation capability of cartilage tissue is one of the frequent problems encountered by the dentist and orthopedic surgeons. Acacia nilotica commonly known as (babul, thorny acacia, Egyptian acacia or thorn mimosa) has wide range of medicinal uses. The current study was carried out to investigate the herbal-based chondrogenesis inducing ability of leaves extract of A. nilotica in Mesenchymal stem cells (MSCs). Purpose: To investigate the ability of Acacia nilotica leaves extract in chondrogenesis induction from Mesenchymal stem cells Study design: The experimental were designed according to the completely randomized design (CRD). Methods: Different concentration of water and ethanol extract of plant leaves were tested for its inhibitory activity on HDP-SC. The HDP-SCs were stimulated to differentiate into chondrocytes in the presence of water extract of A. nilotica leaves. The study was accomplished by assessing the glycosaminoglycan (GAG), aggrecan, collagen 2α1 (Col2α1), and sox9 in the cellular matrix required for cartilage tissue formation. The MSCs revealed surface markers like CD45, CD90, CD105, and CD166 cultured on specialized chondrogenic differentiation medium in presence of leaves extract of A. nilotica. Results: The aqueous leaves extract showed a time-dependent increase in the concentration of glycosaminoglycan (GAG) deposition on 7th, 14th, and 21st day of incubation. The chondrogenic specific markers like aggrecan and col2α1were up-regulated from 7th to 21st days of incubation showing the highest protein expression on the 21st day. The sox9 protein was substantially enhanced on the 7th to 21thday of incubation of HDP-SC with leaves extract of A. nilotica compared to standard TGF-β inducer. Conclusion: The results demonstrate that aqueous leaves extract of A. nilotica promotes chondrogenesis of Mesenchymal stem cells. The study suggests that water leaves extract of "Babool''can be used as an alternative strategy for treatment of dental pulp through chondrogenic differentiation. A. nilotica as a source of many active secondary metabolites which may serve as potential candidates for development of novel lead compounds. This research confirmed the usefulness of this plant A. nilotica as a characteristic feature of medical plant and pharmaceutical. Further studies in the future are required to identify the role of the rest of the active compounds.